For the function \( f \), given below, find the antiderivative \( F \) that satisfies \( F(1)=2 \). \( f(x)=x^{3}-4 x^{-2}+3 \) The antiderivative that satisfies the given condition is \( F(x)=\square \).
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To find the antiderivative \( F(x) \), we start by integrating the function \( f(x) = x^3 - 4x^{-2} + 3 \). \[ F(x) = \int (x^3 - 4x^{-2} + 3) \, dx \] Integrating each term separately, we get: \[ F(x) = \frac{x^4}{4} - 4 \cdot \left(-\frac{1}{x}\right) + 3x + C = \frac{x^4}{4} + \frac{4}{x} + 3x + C \] Now we need to determine \( C \) such that \( F(1) = 2 \). \[ F(1) = \frac{1^4}{4} + \frac{4}{1} + 3 \cdot 1 + C = \frac{1}{4} + 4 + 3 + C \] \[ F(1) = \frac{1}{4} + 7 + C = \frac{29}{4} + C \] Setting \( F(1) = 2 \): \[ \frac{29}{4} + C = 2 \] \[ C = 2 - \frac{29}{4} = \frac{8}{4} - \frac{29}{4} = -\frac{21}{4} \] Thus, the antiderivative \( F(x) \) that satisfies \( F(1) = 2 \) is: \[ F(x) = \frac{x^4}{4} + \frac{4}{x} + 3x - \frac{21}{4} \] So we can conclude: The antiderivative that satisfies the given condition is \( F(x) = \frac{x^4}{4} + \frac{4}{x} + 3x - \frac{21}{4} \).